Effectiveness of Nutritional Advice for Community-Dwelling Obese Older Adults With Frailty: A Systematic Review and Meta-Analysis - Yin, Yue-Heng; Liu, Justina Yat Wa; Fan, Tsz Man; Leung, Kit Man; Ng, Man Wai; Tsang, Tsun Yee; Wong, Ka Po; Välimäki, Maritta (Frontiers in Nutrition, 2021)
Objectives: This systematic review aims to examine the effectiveness of nutritional advise interventions compared with usual care or exercise or exercise combined with nutritional advice as a means of improving the body weight, body composition, physical function, and psychosocial well-being of frail, obese older adults. Methods: Searches were made of CINAHL, Cochrane Library, Embase, MEDLINE, PsycINFO, and Scopus databases in order to identify relevant studies. The quality of the included studies was assessed using Cochrane’s risk of bias tool 2. Meta-analysis was performed in respect of body weight and fat mass. Other outcomes were synthesized narratively. Results: Eight articles (from two studies) with a total of 137 participants were included in the review. The results revealed that nutritional advice was more effective than exercise in reducing body weight and fat mass. The nutritional advice was also beneficial in enhancing physical function and psychosocial well-being. However, it was less effective than exercise or combined interventions in increasing muscle strength and preventing lean mass loss. Conclusions: Nutritional advice is an essential intervention for reducing body weight and fat mass, for enhancing the physical function, and for improving the psychosocial well-being of obese older adults experiencing frailty. The limited numbers of studies included in this reviews suggests that there is a need for more well-designed interventional studies in order to confirm these findings. Key Words: nutritional advice, frailty, obesity, body weight, physical function